Effect of grasshopper meal on laying hens’ performance and eggs quality characteristics - BRAH, NOURI; ISSA, SALISSOU; HOUNDONOUGBO, FRÉDÉRIC M (The Indian Journal of Animal Sciences, 2017)
The purpose of this study was to investigate the potential effects of gradually substituting fish meal by grasshopper meal in laying hens diets. Laying performance and egg quality were evaluated during 4 months on 140 laying hens ISA Brown of 20-week age with an average initial body weight of 1,386±10 g at the beginning of the experiment. Layers were fed 5 diets in which fish meal was gradually replaced by grasshopper meal. The hens were randomly allotted into 20 pens with 4 pens (repetitions)/feed and 7 hens/pen. The fish meal (FM) was replaced by the grasshopper meal (GM) in the proportion of 0, 25, 50, 75 and 100% to obtain G0 (Control), G25 (25% GM + 75% FM), G50 (50% GM + 50% FM), G75 (75% GM+ 25% FM) and G100 (100% GM+ 0% FM). During the 4 months experiment lasted, laying rate, daily feed intake, feed efficacy and efficiency, eggs weight and shape index, albumen height and egg shell thickness were statistically insignificant (P>0.05) for all birds. In addition, diets containing grasshopper meal (G25, G50, G75 and G100) improved egg yolk colour and Haugh unit compared to the control diet (G0). Therefore, Niger poultry farmers could replace fishmeal by grasshopper meal in the diets of laying hens.